2011
DOI: 10.4103/0019-5049.82673
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic response to endotracheal intubation in coronary artery disease: Direct versus video laryngoscopy

Abstract: Endotracheal intubation involving conventional laryngoscopy elicits a haemodynamic response associated with increased heart and blood pressure. The study was aimed to see if video laryngoscopy and endotracheal intubation has any advantages over conventional laryngoscopy and endotracheal intubation in patients with coronary artery disease. Thirty patients suffering from coronary artery disease scheduled for elective coronary artery bypass grafting (CABG) were studied. The patients were randomly allocated to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 22 publications
3
81
2
1
Order By: Relevance
“…Different results obtained by Muralidhar Kanchi, et al [17] in their study hemodynamic changes were not different between the groups. They concluded that video laryngoscopy did not provide any benefit in hemodynamic response to laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 42%
“…Different results obtained by Muralidhar Kanchi, et al [17] in their study hemodynamic changes were not different between the groups. They concluded that video laryngoscopy did not provide any benefit in hemodynamic response to laryngoscopy and intubation.…”
Section: Discussionmentioning
confidence: 42%
“…[20,[25][26][27] These results suggest that the passage of the tracheal tube through the vocal cords and tracheal stimulus is the main cause of the hemodynamic response to endotracheal intubation. [2,22,26,28] A majority of studies have demonstrated that laryngoscopy time was significantly longer in GlideScope however we found no significant difference between the groups in our study. Studies claim that longer intubation time in the GlideScope group may counterbalance the favorable effect of reduced laryngoscope lifting force.…”
Section: Macintoshcontrasting
confidence: 54%
“…Similar results of intubation time were found in the study done by Kanchi et al on coronary artery disease patients undergoing revascularization. 6 There are some limitations of the study, firstly we acknowledge the potential for bias exists as it was impossible to blind the anaesthesiologist to the device being used, secondly the relative efficacy of these device with the other promising devices such as Airtraq, McCoy, McGrathw, Bonfils, Bullard laryngoscopes have not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…The AWS is operated by two AA batteries which allow almost 1 hour of operating time. 6 It is not known if this device offers any particular advantage in terms of hemodynamic stability when compared to conventional direct laryngoscopy in patients. The study was designed with the objective to assess the hemodynamic changes that occur during and after endotracheal intubation with video laryngoscope and comparing those changes with conventional laryngoscopy.…”
Section: Introductionmentioning
confidence: 99%